PENINGKATAN WAWASAN PETANI TENTANG PERAN KELOMPOK TANI DALAM PENGEMBANGAN USAHATANI KELAPA SAWIT RAKYAT - Nainggolan, Hotden Leonardo; Tampubolon, Jongkers; Ginting, Albina; M. H. Siahaan, Toga (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This community service activity was carried out in Sumbul Village, Subdistrict of STM Hilir, District of Deli Serdang, in November 2020. This activity was attended by 20 smallholder oil palm farmers as participants. This service activity uses the method; participatory empowerment through counseling, discussion and ending with evaluation. Based on the counseling activities, it is concluded; a) there is an increase in the insight of farmers related to the application of technology in the development of smallholder oil palm farming through their participation in farmer groups from 30% to 80%, b) there is an increase in the insight of farmers from 35% of participants to 75% who understand that with involvement in farmer groups it will be easy to access farming technology, c) there is an increase in the insight of farmers from 15% of participants to 90% who understand that by being involved in farmer groups will help them in implementing smallholder oil palm farming technology, d) there is an increase in the insight of farmers from 25% of participants to 80 % who understand that the application of farming technology will encourage the development of smallholder oil palm farming better.